2015
DOI: 10.11113/mjfas.v11n2.356
|View full text |Cite
|
Sign up to set email alerts
|

Effect on silicon nitride thin films properties at various pressure of R.F. magnetron sputtering

Abstract: Silicon nitride is a well-known kind of material with numerous applications such as gate dielectrics and etch-masks in semiconductor device fabrication, anti reflective coatings in solar panel manufacturing and optical waveguides in biosensing fields. In this work, Silicon nitride thin films were prepared using radio frequency (R.F.) magnetron sputtering technique at room temperature. The properties of thin films were investigated with respect to sputtering-gas pressure during film deposition. The produced thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, the Magnetron sputtering technique has considerable advantages over the PECVD technique due to the absence of toxic gases, low temperature deposition, easy to tune deposition rate and simple deposition system [17]. The conventional parameters for thin film deposition are sputtering powers [18] and sputtering pressures [19,20]. However, it is reported that the thin film properties can be varied by altering target to substrate distance while keeping the sputtering power and pressure fixed [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the Magnetron sputtering technique has considerable advantages over the PECVD technique due to the absence of toxic gases, low temperature deposition, easy to tune deposition rate and simple deposition system [17]. The conventional parameters for thin film deposition are sputtering powers [18] and sputtering pressures [19,20]. However, it is reported that the thin film properties can be varied by altering target to substrate distance while keeping the sputtering power and pressure fixed [21].…”
Section: Introductionmentioning
confidence: 99%